2018
DOI: 10.5194/acp-2018-686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large contrast in the vertical distribution of aerosol optical properties and radiative effects across the Indo-Gangetic Plain during SWAAMI-RAWEX campaign

Abstract: <p><strong>Abstract.</strong> Measurements of the vertical profiles of the optical properties (namely the extinction / scattering and absorption coefficients; respectively σ<sub>ext</sub> / σ<sub>scat</sub> / σ<sub>abs</sub>) of aerosols have been made across the In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Hence it is imperative to examine altitudinal dependency of CCN on ground (identified by the colour) for each day of observation (identified by the shape of the point). Central IGP showed highest absorption coefficient (column averaged) of 26 ± 9 Mm -1 , followed 5 by west (16 ± 2 Mm -1 ) and east (15 ± 3 Mm -1 ) IGP (Vaishya et al, 2018). It is interesting to note that the linear relationship is maintained for low to moderate concentrations of BC (up to around 1000 ng m -3 , which occurs mostly above PBL), while significant scatter occurs for higher values of BC (exceeding 2000 ng m -3 ), which occurs mostly in the lower altitudes, supporting the hypothesis.…”
Section: Altitudinal Dependence Of Ccn -Cn Associationmentioning
confidence: 95%
See 2 more Smart Citations
“…Hence it is imperative to examine altitudinal dependency of CCN on ground (identified by the colour) for each day of observation (identified by the shape of the point). Central IGP showed highest absorption coefficient (column averaged) of 26 ± 9 Mm -1 , followed 5 by west (16 ± 2 Mm -1 ) and east (15 ± 3 Mm -1 ) IGP (Vaishya et al, 2018). It is interesting to note that the linear relationship is maintained for low to moderate concentrations of BC (up to around 1000 ng m -3 , which occurs mostly above PBL), while significant scatter occurs for higher values of BC (exceeding 2000 ng m -3 ), which occurs mostly in the lower altitudes, supporting the hypothesis.…”
Section: Altitudinal Dependence Of Ccn -Cn Associationmentioning
confidence: 95%
“…The efficacy of the inlet to sample aerosols below 4 μm, under such conditions, has been demonstrated during the DC-8 Inlet Characterization Experiment (McNaughton et al, 2007). Further details of the experimental setup are explained in Babu et al, (2016) and Vaishya et al, (2018). The air, aspirated through this inlet, is then fed to different instruments through a manifold.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only six different profiles are presented, and only one pair of these consists of measurements made before and during the monsoon at the same location. Many other studies have explored monsoon-aerosol interactions over India using aircraft data (see Li et al, 2016 )-including an analysis of measurements from the same period as the present manuscript (Vaishya et al, 2018)-and it is not clear to me what makes the data presented in the present work particularly unique. Moreover, the supporting RF and heating rate calculations that are provided do not seem to generate novel insights.…”
mentioning
confidence: 90%
“…For example, Schwarz et al (2008) conducted aircraft-based BC measurements in Costa Rica. Vaishya et al (2018) reported vertically resolved light absorption profiles at Indo-Gangetic Plain (IGP) using aircraft measurements and found significant atmospheric warming induced by BC. Wang et al (2018a) found a decreasing trend of light absorption with height within 0-3 km, and the light absorption vertical profiles were influenced by the evolution of a boundary layer.…”
Section: Introductionmentioning
confidence: 99%